Characterization of Different Cultivars of Mango Commercially Grown in Malda, India - Khara, S N; Thakur, Pran Krishna; Acharya, Pinaki; Dhua, R S (Journal of Postharvest Technology, 2016)
Fruits of eighteen mango varieties (Amrapali, Ashwina, Fazli, Gopalbhog,  Khirshapati, Lakshmanbhog, Langra, Baishakhi Gooti, Rakhalbhog, Golapkhas,  Ashudagi, Arajanma, Mallika, Krishanbhog, Michrikanta, Laxmibhog, Phunia and  Brindabani) were collected from eight mango growing blocks of two Sub-divisions  of Malda district. Both physico-chemical parameters were assessed at optimum  ripening condition of fruits. Among the mango cultivars, the fruits of Fazli and  Mallika were superior to others with regard to fruit weight and size. Phunia was the smallest in weight and size. The proportion of edible portion was highest in cv.  Lakshmanbhog and was lowest in Michrikanta. In the present investigation, the  maximum percent of total soluble solids was in cv. Mallika of 23.60 and minimum  of 12.80 in cv. Lakshmanbhog. The total sugar, reducing sugar as well as non reducing sugar contents was maximum in cv. Mallika. The acidity of fruits varied  from 0.15 –0.35%. The highest content of ascorbic acid was recorded in cv. Langra  (56.34 mg / 100g). The highest TSS :Acid ratio was also recorded in the mango  cvs. Mallika, Brindabani, Amrapali, Aswina, Gopalbhog, Rakhalbhog, Ashudagi  and Kishanbhog. The highest and lowest amount of β-carotene was recorded in cv.  Kishanbhog (17897 µg/100g) and cv. Brindabani (1089 µg/100g), respectively.  The fruits of cv. Lakshmanbhog though contains lowest TSS:Acid as compared to  Mallika (157.33), but have good attractive appearance, firm fruit, good keeping and transport quality, optimum size and shape, high fibreless edible proportion. The cv. Langra with high TSS : Acid (55.88) is one of the most popular cultivars of India.  Thus, considering the fruit qualities, it was observed that some of the lesser known  varieties viz. Michrikanta, Phunia, Ashudagi, Arajanma etc. have great potential for  commercial exploitation. Also, regular bearing cultivar ‘Laxhmanbhog’ having  good fruit quality and attractive colour could be a potent variety for export from the  state.
Keywords: Mangifera indica L; Fruit quality; Cultivar variation; Postharvest quality; Export potential